The Use of Junfeng BFS Water (JBW) in Dry Eye Syndrome - Eisenmann, Dieter; Liu, Yuying; Renieri, Giulia; Thieme, Hagen (Klinische Monatsblätter für Augenheilkunde, 2019)
Background and Purpose Junfeng BFS Water (JBW) is normal drinking water treated by an extremely low frequency electromagnetic field with certain electromagnetic oscillations. This leads to a change in physical water properties, such as an increase in permittivity and an increase in dissolved oxygen. Animal studies show that JBW has certain biological effects, such as improvement in microcirculation, cell hydration, and blood rheology. In a clinical study, we were able to show an improvement in ocular blood flow after drinking JBW. Since people drinking JBW reported an improvement in dry eye symptoms, we wanted to examine tear film stability by determining the break-up time (BUT) through patient interviews.Methods Sixty patients (120 eyes) were age matched and randomized in a double-blind study using the JBW device, or an identical looking nonworking device, without influence on drinking water (control group). All participants had to drink 2 liters of water per day over a period of 2 months. All study subjects underwent a complete ophthalmological examination, including measurement of BUT at day 0, 1 month, and 2 months. At the same time, the patients were interviewed about their eyes, their subjective feelings, and their vision. Statistical analysis was performed using the IBM SSPS program. Bivariate statistics were performed using the ANOVA test. The level of significance was a = 0.05Results The increase in BUT was significantly higher in both eyes (a< = 0.01) of the population drinking JBW after 1 and 2 months compared to the control group using untreated water. This result was confirmed in patient interviews. Therefore, patients drinking JBW judged the question “do you have tired eyes?” significantly better (a = 0.04) than the control group after 1 month. Eighty percent of the JBW group continued to drink JBW 6 months after the end of the study, and more than 50% were able to reduce treatment with artificial tears or stop it completely.Conclusions Apart from an improvement in microcirculation, drinking JBW seems to have a positive effect on dry eye syndrome. Mechanisms are still unknown, and improvement in microcirculation of the lacrimal gland should be discussed. If our results can be confirmed in a larger study, and with more sophisticated methods, we see a potential for JBWʼs use as an additive to conventional dry eye therapy.
Keywords: Junfeng BFS water; break-up-time; dry eye syndrome; microcirculation; dry eye therapy